Overwhelming sepsis in a neonate affected by Zellweger syndrome due to a compound heterozygosis in PEX 6 gene: a case report - Laura Lucaccioni; Beatrice Righi; Greta Miriam Cingolani; Licia Lugli; Elisa Della Casa; Francesco Torcetta; Lorenzo Iughetti; Alberto Berardi (BMC, 2020)
Abstract Background Peroxisome biogenesis disorders (PBDs) are a group of metabolic diseases caused by dysfunction of peroxisomes. Different forms of PBDs are described; the most severe one is the Zellweger syndrome (ZS). We report on an unusual presentation of Zellweger syndrome manifesting in a newborn with severe and fulminant sepsis, causing death during the neonatal period. Case presentation A term male Caucasian neonate presented at birth with hypotonia and poor feeding associated with dysmorphic craniofacial features and skeletal abnormalities. Blood tests showed progressive leukopenia; ultrasounds revealed cerebral and renal abnormalities. He died on the fourth day of life because of an irreversible Gram-negative sepsis. Post-mortem tests on blood and urine samples showed biochemical alterations suggestive of ZS confirmed by genetic test. Conclusions ZS is an early and severe forms of PBDs. Peroxisomes are known to be involved in lipid metabolism, but recent studies suggest their fundamental role in modulating immune response and inflammation. In case of clinical suspicion of ZS it is important to focus the attention on the prevention and management of infections that can rapidly progress to death.